2018
DOI: 10.1007/s00737-018-0889-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain plasticity in pregnancy and the postpartum period: links to maternal caregiving and mental health

Abstract: Pregnancy and the postpartum period involve numerous physiological adaptations that enable the development and survival of the offspring. A distinct neural plasticity characterizes the female brain during this period, and dynamic structural and functional changes take place that accompany fundamental behavioral adaptations, stimulating the female to progress from an individual with self-directed needs to being responsible for the care of another life. While many animal studies detail these modifications, an em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 113 publications
(135 reference statements)
2
119
0
2
Order By: Relevance
“…The study revealed activation of the PAG in mother viewing their own child vs. other child, whatever was the context (Noriuchi et al 2008), indicating that the PAG could be involved in social object recognition or bond attachment. These results -together with other studies on animals showing the involvement of the PAG in maternal behaviors including defense (Moura et al 2010;Sukikara et al 2010;Klein et al 2014;Barba-Muller et al 2018) -support that the PAG might be viewed as an important brain structure of the caregiving parental brain ).…”
Section: Emotions and The Pag: How In Vivo Imaging Changed Our View?supporting
confidence: 75%
“…The study revealed activation of the PAG in mother viewing their own child vs. other child, whatever was the context (Noriuchi et al 2008), indicating that the PAG could be involved in social object recognition or bond attachment. These results -together with other studies on animals showing the involvement of the PAG in maternal behaviors including defense (Moura et al 2010;Sukikara et al 2010;Klein et al 2014;Barba-Muller et al 2018) -support that the PAG might be viewed as an important brain structure of the caregiving parental brain ).…”
Section: Emotions and The Pag: How In Vivo Imaging Changed Our View?supporting
confidence: 75%
“…Decrease in brain size begins after placental implantation 25 . It reaches maximum at term and it endures for at least 2 years post-partum 25,26 . Structural and functional changes accompany fundamental behavioural adaptations, stimulating to progress from self-involved individuality to carying motherhood 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It reaches maximum at term and it endures for at least 2 years post-partum 25,26 . Structural and functional changes accompany fundamental behavioural adaptations, stimulating to progress from self-involved individuality to carying motherhood 26 . Changes in the maternal brain during pregnancy cannot be explained by endocrine and environmental factors alone 27 .…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, functional plasticity is mediated predominantly by hormonal changes, however; during the postpartum period, the functional plasticity is primarily driven by the social experience of interacting with the infant . This functional plasticity supports the ability of the mother to link sensory cues to the underlying needs of the infant and respond in a prompt and appropriate manner . This experience‐dependent plasticity functions to modulate the maternal brain circuitry and facilitate the ongoing interactions with the infant .…”
Section: Introductionmentioning
confidence: 97%
“…8 This functional plasticity supports the ability of the mother to link sensory cues to the underlying needs of the infant and respond in a prompt and appropriate manner. 9 This experience-dependent plasticity functions to modulate the maternal brain circuitry and facilitate the ongoing interactions with the infant. 3 However, the relationship between postpartum months and rsFC in the postpartum period remains unclear.…”
mentioning
confidence: 99%